Training On Cervical Cancer And HPV Vaccine For 9-13 Years’ Adolescent Girls, A Community Service - Tesfalem Tilahun Yemane (International Journal Of Community Service, 2024)
The aims of this community service project was to raise awareness about cervical cancer and the importance of HPV vaccine for 9-13 years old girls and their parents. The training was designed to address the knowledge gap regarding cervical cancer and HPV vaccine among 9-13 years old girls and their parents, we can empower them to make informed decisions about vaccination. Before implementation of training, community survey was conducted. The findings of the survey were help us to identify gaps in knowledge and attitudes and inform the development of training as an intervention. Through training & distributed training materials the outcome of the community service was achieved. The knowledge of school adolescent’s girls was evaluated and improved. The uptake HPV vaccination were increased and all unvaccinated school girls were vaccinated after training. Training participants were empowered to correct any misconceptions with in the community.